Análisis de la disponibilidad y demanda de agua, con fines de riego, en el sistema Campana-Malacatos, utilizando los sistemas de información geográfica (SIG) - Cañar Rivas, Alex Leonel (2016)
The water resource is a determinant factor in the economic and social development and, at the same time, it fulfills the basic function to support the integrity of the natural environment, in addition for being one of the natural vital resources, turns out to be imperative that the water topics are not treated as an isolated form; for what, so much governmental organisms as of the private sector, they have to take decisions complicated on the assignment of the water, due to the fact that they face an offer that diminishes opposite to an increasing demand. At the same time, the factors like the demographic, climatic changes and the lack of information hidrometeorológica in the basins of capture influence directly to the good integral vision of planning of the water resource especially the zones of irrigation. In such a virtue, the present study carries when the water availability estimates in the basin of the river Bell up to the site of capture, to analyze the water demand of the cultures; and, to confront the offer and water demand, with ends of irrigation in the perspective to structure alternatives for his optimization. The water availability with ends of irrigation and the water consumption of the cultures in the system of irrigation Campana-Malacatos, located in the canton Loja to the south of Ecuador, they were estimated by means of empirical indirect methods: rational method, ecological polynomial and of the coefficient of run-off calculated, and the adjustment of the method Hargreaves respectively. In addition with the purpose of being able to determine the empirical method that more adjusts to the conditions of the basin of the system of irrigation, appraisals of flow were realized in an interval of time (eight days) in the point of capture. The methodology that better adjusted to the conditions of the basin in study was the rational method, the same one who allowed estimating a water availability in the point of capture of 0.68 m3/s to a probability of 75 %. The water demand of the crops was of 0.578 m3/s to irrigate 743 hectares. With the available flow, it is possible to increase, already it is 96,3 it hectares of irrigation for ruts with an efficiency of application of 50 %, 516,0 it hectares of irrigation for aspersion to an efficiency of 75 %; ó an area of 767,8 hectares, of irrigation for drip to 90 % of efficiency of application. Finally, the present investigation leaves valuable information for the planning and sustainability of the system of irrigation Campana-Malacatos.